The Impact of Sanming Healthcare Reform on Antibiotic Appropriate Use in County Hospitals in China - Hu, Lin; Fu, Mengyuan; Wushouer, Haishaerjiang; Ni, Bingyu; Li, Huangqianyu; Guan, Xiaodong; Shi, Luwen (Frontiers in Public Health, 2022)
Background The excessive use of resources and poor quality of care are great concerns worldwide, particularly in China. In 2013, a model of systematic reforms was developed in Sanming to address the inefficiency and waste in public hospitals. However, limited empirical studies have evaluated the effect of Sanming healthcare reform on antibiotic appropriate use. This study aims to evaluate the impact of the healthcare reform on the appropriate use of antibiotics in county-level public hospitals in Sanming, China. Methods We conducted a retrospective observational study exploring trends in antibiotic use with an interrupted time series design. We selected three county-level hospitals in Sanming and extracted outpatient prescriptions of the Departments of Internal Medicine and the Department of Pediatrics between January 2011 and December 2017. Acute Upper Respiratory Tract Infection (AURI), Acute Bronchitis (AB) and Community Acquired Pneumonia (CAP) were selected as the sample diseases for our analysis. The primary outcome was the percentage of prescriptions conformed with standard treatment guidelines (STGs). Results A total of 142,180 prescriptions were included in the analysis. During the study period, the percentage of antibiotics prescriptions conformed with STGs boosted from 32.4% in 2011 to 82.3% in 2017. Moreover, after the reform, the rate of prescriptions that conformed with STGs showed significant increasing trends in children with AURI (β=1.624, p<0.001), children with AB (β=3.123, p<0.001), adult with AB (β=1.665, p<0.001), children with CAP (β=3.123, p<0.001), adult with CAP (β=4.385, p<0.001), but not in adult patients with AURI (β=-0.360, p=0.022). Conclusion Our study confirmed that the Sanming healthcare reform helped to promote the appropriate use of antibiotics in county-level hospitals. This systematic approach to healthcare reform, characterized by an effective governance structure, dynamic financial compensation mechanisms, and specialized drug stewardship, is promising for future public hospital reforms.